ALEXANDER FEINBERG'S POEMS GIVE INFORMATION ABOUT HIS NATURE (World Bulletin of Social Sciences, 2023)
The life of Russian and Uzbek poet Alexander Feinberg is described in this article, along with his final years' experiences, in the language of his contemporaries. Reading the piece allows one to fully comprehend the poet's personal traits and commitment to his country. The poet's life is like a book; the more you read it, the more of its core is exposed, according to those who spoke with Feinberg